2005
DOI: 10.1007/s10720-005-0120-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Property Relations in Barium Borate Glasses from Raman Scattering Data

Abstract: Glasses in the x BaO-(100x )B 2 O 3 system ( x = 16-50 mol %) are investigated by Raman spectroscopy. The spectral forms of stoichiometric groupings are separated from the experimental Raman spectra. The diagram of the content of these groupings in glasses is constructed. The diagram obtained makes it possible to calculate the densities, refractive indices, temperature coefficients of linear expansion, and fractions of fourfold-coordinated boron atoms with the use of the experimentally determined partial prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…According to our data, the concentration of the BO 4 tetrahedrons is 44 ± 4% in the binary barium diborate glass. This value is in good compliance with the data of other authors obtained by IR [13] and Raman spec troscopy [14]. The addition of aluminum oxide is accompanied by a decrease in the fraction of borate tetrahedrons of up to 13 ± 5% for the glass with the highest Al 2 O 3 content (sample 50ABB).…”
Section: Legendsupporting
confidence: 91%
“…According to our data, the concentration of the BO 4 tetrahedrons is 44 ± 4% in the binary barium diborate glass. This value is in good compliance with the data of other authors obtained by IR [13] and Raman spec troscopy [14]. The addition of aluminum oxide is accompanied by a decrease in the fraction of borate tetrahedrons of up to 13 ± 5% for the glass with the highest Al 2 O 3 content (sample 50ABB).…”
Section: Legendsupporting
confidence: 91%
“…Markova et al reported [49] that in BaO-B 2 O 3 glasses boson peak frequency and intensity increases with rise in T g . But in the present study, peak intensity increases and T g decreases with increase in Bi 2 O 3 mol%.…”
Section: Ft-raman Spectramentioning
confidence: 99%
“…2-5, 7, and 9 these intensities were multiplied by Vn 2 because variation of molar volume (in dependence on glass composition) will result in changing of quantity of scattering centers in the laser beam and, on the other hand, refractive index will vary the aperture of collection of scattered radiation. Details of the measurement procedure are described elsewhere [38,39]. Powders of glasses were crystallized in an electrical furnace using appropriate temperature-time conditions.…”
Section: Methodsmentioning
confidence: 99%